إحياء الأرض الموات في المنظور الإسلامي - كاظم, فوزي خيري; سلمان, هديل كاظم (lark, 2019)
Summary:The revival of the earth is the most important issue emphasized by the Islamic law , Because of their great economic importance to the individual and society at large It helps to invest these idle lands for some reason, As well as it greatly reduces the size of unemployment because of the availability of several jobs. It also contributes significantly to increasing economic resources that benefit the nation. And to learn how to invest these lands and the mechanism of reviving them in Islam, We have taken it as the subject of our research: "Reviving the Land of the Right in the Islamic Perspective". We have followed the most important subjects of the Islamic law, The scholars - from various schools of jurisprudence - are the most important
Keywords: Minerals; Jurists; Engraving; gangrene; Land; Revival